2023
DOI: 10.1002/advs.202305566
|View full text |Cite
|
Sign up to set email alerts
|

CAR‐Aptamers Enable Traceless Enrichment and Monitoring of CAR‐Positive Cells and Overcome Tumor Immune Escape

Hang Zhou,
Tuersunayi Abudureheman,
Wei‐Wei Zheng
et al.

Abstract: Chimeric antigen receptor (CAR)‐positive cell therapy, specifically with anti‐CD19 CAR‐T (CAR19‐T) cells, achieves a high complete response during tumor treatment for hematological malignancies. Large‐scale production and application of CAR‐T therapy can be achieved by developing efficient and low‐cost enrichment methods for CAR‐T cells, expansion monitoring in vivo, and overcoming tumor escape. Here, novel CAR‐specific binding aptamers (CAR‐ap) to traceless sort CAR‐positive cells and obtain a high positive r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…A previous study has shown that the CD8 + T cell-binding aptamer A3t combined with magnetic beads is an excellent choice for achieving the traceless enrichment of CD8 + T cells. Indeed, this approach not only reduces costs but also simplifies the purification process. , Additionally, our previous study identified a type of CAR-aptamers that could efficiently accomplish the traceless enrichment of CAR + T/NK cells. , In fact, the process of aptamer capture and release does not leave markers or reduce cell viability. We thus speculated that the combination of aptamers with magnetic beads is an economical and convenient method for enriching target cells such as CD8 + T cells.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study has shown that the CD8 + T cell-binding aptamer A3t combined with magnetic beads is an excellent choice for achieving the traceless enrichment of CD8 + T cells. Indeed, this approach not only reduces costs but also simplifies the purification process. , Additionally, our previous study identified a type of CAR-aptamers that could efficiently accomplish the traceless enrichment of CAR + T/NK cells. , In fact, the process of aptamer capture and release does not leave markers or reduce cell viability. We thus speculated that the combination of aptamers with magnetic beads is an economical and convenient method for enriching target cells such as CD8 + T cells.…”
Section: Resultsmentioning
confidence: 99%